PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA GAMBAR TERHADAP KETERAMPILAN MENULIS KARANGAN EKSPOSISI SISWA KELAS X SMA EKASAKTI PADANG - Zuraida Khairani; Dwi Mutia Chan; Najmi Hayati (STKIP Pesisir Selatan, 2022)
The purpose of this research. First, it describes the writing skills of exposition essays for class X students of SMA Negeri Ekasakti Padang before applying the Problem Based Learning (PBL) model assisted by media images. Second, it describes the exposition essay writing skills of class X SMA Ekasakti Padang after applying the Problem Based Learning (PBL) model assisted by media images. Third, analyzing the effect of Problem Based Learning (PBL) assisted by media images on the exposition essay writing skills of class X SMA Ekasakti Padang. This type of research is quantitative research. The results of data analysis and discussion are. First, the exposition writing skills of class X.2 SMA Ekasakti Padang before applying the Problem Based Learning (PBL) model assisted by media images were in the